Nociceptive DRG neurons express muscle lim protein upon axonal injury - Evgeny Levin (Nature Portfolio, 2017)
Abstract Muscle lim protein (MLP) has long been regarded as a cytosolic and nuclear muscular protein. Here, we show that MLP is also expressed in a subpopulation of adult rat dorsal root ganglia (DRG) neurons in response to axonal injury, while the protein was not detectable in naïve cells. Detailed immunohistochemical analysis of L4/L5 DRG revealed ~3% of MLP-positive neurons 2 days after complete sciatic nerve crush and maximum ~10% after 4–14 days. Similarly, in mixed cultures from cervical, thoracic, lumbar and sacral DRG ~6% of neurons were MLP-positive after 2 days and maximal 17% after 3 days. In both, histological sections and cell cultures, the protein was detected in the cytosol and axons of small diameter cells, while the nucleus remained devoid. Moreover, the vast majority could not be assigned to any of the well characterized canonical DRG subpopulations at 7 days after nerve injury. However, further analysis in cell culture revealed that the largest population of MLP expressing cells originated from non-peptidergic IB4-positive nociceptive neurons, which lose their ability to bind the lectin upon axotomy. Thus, MLP is mostly expressed in a subset of axotomized nociceptive neurons and can be used as a novel marker for this population of cells.